Comparative cost-effectiveness of first-line pembrolizumab plus chemotherapy vs. chemotherapy alone in persistent, recurrent, or metastatic cervical cancer - Lin, Ying-tao; Wang, Chang; He, Xiao-yan; Yao, Qi-min; Chen, Jian (Frontiers in Immunology, 2024)
Abstract Background: Treating persistent, recurrent, or metastatic cervical cancer remains challenging. Although pembrolizumab, combined with chemotherapy and bevacizumab, offers a promising first-line option, its cost-effectiveness within the Chinese healthcare system has not been established. Methods: A partitioned survival model was constructed using patient data from the KEYNOTE-826 trial. Efficacy, safety, and economic data from both trial and real-world practices were utilized to determine the costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratio (ICER) of the treatment strategies. Comprehensive insights were gained through the sensitivity and subgroup analyses. Results: Over five years, the combination of pembrolizumab, chemotherapy, and bevacizumab offered an additional 1.18 QALYs compared to that provided by standard treatments. This regimen increased the costs by US$ 134,502.57, resulting in an ICER of US$ 114,275.67 per QALY, relative to traditional treatment costs. The ICER for the pembrolizumab regimen was further calibrated to be US$ 52,765.69 per QALY. Both ICER values surpassed China's established willingness-to-pay threshold. Importantly, subgroup analysis revealed enhanced cost-effectiveness in patients presenting with a programmed death-ligand 1 combined positive score (PD-L1 CPS) ≥10. Conclusion: Introducing pembrolizumab alongside chemotherapy and bevacizumab may not be a cost-effective primary strategy for advanced cervical cancer against current standards. However, for patients with a PD-L1 CPS ≥10, the therapeutic and economic outcomes could be improved by adjusting the pembrolizumab price.